2013
DOI: 10.1021/ma401311s
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on Structure–Property Relationships for Conjugated Microporous Polymers: The Importance of Rings and Strain

Abstract: The photophysical properties of insoluble porous pyrene networks, which are central to their function, differ strongly from those of analogous soluble linear and branched polymers and dendrimers. This can be rationalized by the presence of strained closed rings in the networks. A combined experimental and computational approach was used to obtain atomic scale insight into the structure of amorphous conjugated microporous polymers. The optical absorption and fluorescence spectra of a series of pyrene-based mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
(96 reference statements)
2
39
0
Order By: Relevance
“…To gain insight into the influence of the nature of the chromophores on their electronic structure and the corresponding molecular frontier orbitals, DFT calculations were performed on molecular cluster models . Here we anticipated that the molecular frontier orbitals of the constitutive molecular unit are representative of those of the solids.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the influence of the nature of the chromophores on their electronic structure and the corresponding molecular frontier orbitals, DFT calculations were performed on molecular cluster models . Here we anticipated that the molecular frontier orbitals of the constitutive molecular unit are representative of those of the solids.…”
Section: Resultsmentioning
confidence: 99%
“…This modular philosophy, where the molecular building blocks encode the target function, also applies to electronic properties. For instance, electronic structure calculations for photocatalytic CMPs (24,25) showed that the electronic properties of the polymer can be represented by small clusters of just a few monomer units (26).…”
Section: Modular Design Of Functionmentioning
confidence: 99%
“…Such a blue shift is a well-known artefact 65 of the use of range-separated functionals such as ωB97X, which avoid issues with the description of charge-transfer states, but at the expense of slightly blue shifting the overall spectrum. Indeed, in previous work 5,66 we have often applied a rigid ad hoc shift to correct for this, though we do not do that here. The second and more interesting observation is that, if we assume that the evolution of the experimental UV-Vis spectrum after addition of GdL is due to aggregation, experiment and our calculations agree on both the absence of large shifts in the spectrum upon aggregation and the decrease in absorption intensity.…”
Section: Experimental Uv-vis Spectramentioning
confidence: 99%